Intervenções do terapeuta ocupacional junto a pessoas com transtorno do espectro do autismo: uma revisão de escopo - OLIVEIRA, Bruna Thayane Ferreira de (2023)
This study aimed to carry out a scope review, mapping the national literature on occupational therapeutic action with people with ASD. The methodology used for this study was a scope review. The PRISMA checklist was used to guide the research. The search was carried out in Scielo, Web of Science and Embase databases, in national occupational therapy journals (Occupational Therapy Journals, Journal of Occupational Therapy at USP, Brazilian Interinstitutional Journal of Occupational Therapy Revisbra-TO, Bahia Journal of Occupational Therapy) and in the Digital Library of Theses and Dissertations. The literature search was limited to publications on the intervention of Occupational Therapy and ASD, made from 2011 to the present day, providing a result of 375 articles, after applying the inclusion criteria and of exclusion, 8 articles potentially relevant to the study remained. The results demonstrate the importance of the occupational therapist's role with people with ASD, as it favors the processes of social and school inclusion, acts in the acquisition of skills, whether in self-care or gains in mobility. In this way, it is seen during the studies that Occupational Therapy acts in the enhancement of skills and in the participation of these people.